(untitled) (Journal of School Administration Research and Development, 2021)
School superintendents who are African American women are understudied. In this study, researchers explored the lived experiences of African American women superintendents in the state of Texas. The purpose of the study was to identify the challenges, supports, and personal background characteristics that participants believed influenced their ascension to superintendent positions. A phenomenological research approach was used, and data were collected through individual interviews with superintendent participants. Data were analyzed and interpret- ed using Moustakas’ (1994) phenomenological reduction approach. Three major themes emerged in the results: (a) desire to impact others at various levels, (b) sources of personal strength, and (c) external support systems. Subthemes were identified and described for each larger theme. Findings suggest a need to expose aspiring African American women administrators to the challenges and rewards of superintendent positions and increase mentorship opportunities and quality preparation programs.